A high-hardness and high-conductivity Cu-Co-Si alloy and preparation method thereof

By introducing Co elements, performing solid solution treatment and aging treatment in the preparation process of Cu-Co-Si alloy, the problem of difficulty in preparing high-hard and high-conductance Cu-Co-Si alloys in the prior art is solved, and the comprehensive performance of high-hard and high-conductance has been improved and the process has been simplified.

CN119332124BActive Publication Date: 2025-03-18CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411884067.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

It is difficult to prepare Cu-Co-Si alloys with excellent comprehensive performance with high hardness and high conductance.

Method used

By a preparation method, it includes smelting and preparing the alloy raw material components, performing solid solution treatment and aging treatment, and finally post-treatment to obtain the target product. In this method, Co elements are introduced to enhance the solid solubility of Si atoms, and aging treatment promotes the precipitation of Co and Si compounds from the copper alloy, thereby improving conductivity and hardness.

Benefits of technology

The Cu-Co-Si alloy with excellent comprehensive performance with high hardness and high conductivity has been prepared, which improves the conductivity and hardness of the copper matrix and simplifies process operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of alloy heat treatment, and specifically to a high-hardness and high-conductivity Cu‑Co‑Si alloy and a preparation method thereof. The alloy is prepared by the preparation method. The preparation method comprises smelting the alloy raw material components of the required mass percentage to prepare the Cu‑Co‑Si alloy; subjecting the prepared Cu‑Co‑Si alloy to solid solution treatment; subjecting the Cu‑Co‑Si alloy after the solid solution treatment to aging treatment; and subjecting the Cu‑Co‑Si alloy after the aging treatment to post-treatment to obtain the target product. The present invention can prepare a Cu‑Co‑Si alloy with excellent comprehensive performance of high hardness and high conductivity, and has great application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy heat treatment, and in particular to a high-hardness and high-conductivity Cu-Co-Si alloy and a preparation method thereof. Background Art

[0002] High-hardness and high-conductivity copper alloys are widely used in the fields of electronics, electrical engineering, mechanical transportation, etc. due to their excellent comprehensive properties of high hardness and high conductivity. In copper alloys, although the Si element will have a significant strengthening effect on the copper matrix and improve the hardness of the copper matrix, it will significantly reduce the electrical conductivity of the copper matrix. In order to precipitate the Si element in the copper matrix as much as possible, thereby improving the conductivity of the copper matrix, the Co element can be added to form a compound with silicon and precipitate from the copper alloy to improve the conductivity of the copper matrix, while forming a second phase reinforcement to improve the hardness of the copper matrix.

[0003] At present, there are few studies on Cu-Co-Si alloys, and it is difficult to prepare Cu-Co-Si alloys with excellent comprehensive properties of high hardness and high conductivity. Therefore, it is necessary to develop a high hardness and high conductivity Cu-Co-Si alloy and a preparation method thereof. Summary of the invention

[0004] The present invention aims to provide a high-hardness and high-conductivity Cu-Co-Si alloy and a preparation method thereof, which are used to prepare a Cu-Co-Si alloy with excellent comprehensive properties of high hardness and high conductivity. The specific technical scheme is as follows:

[0005] In a first aspect, the present invention provides a method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy, comprising:

[0006] Step S1, melting the alloy raw material components with the required mass percentage to prepare Cu-Co-Si alloy;

[0007] Step S2, subjecting the prepared Cu-Co-Si alloy to a solid solution treatment;

[0008] Step S3, subjecting the Cu-Co-Si alloy after the solution treatment to aging treatment;

[0009] Step S4, post-treating the Cu-Co-Si alloy after the aging treatment to obtain the target product.

[0010] Optionally, the required mass percentage of the alloy raw material components includes a Co content of 1.0% to 3.0%, a Si content of ≤0.8%, a Mg content of ≤0.02%, a P content of ≤0.05%, a Cr content of ≤0.05%, an O content of ≤0.02%, an impurity content of ≤0.05% and a balance of Cu.

[0011] Optionally, the Si content is 0.1%~0.8%; the Mg content is 0.01%~0.02%; the P content is 0.02%~0.05%; the Cr content is 0.02%~0.05%; and the O content is 0.01%~0.02%.

[0012] Optionally, the purity of Co is >99.97%; the purity of Cu is >99.95%; and the purity of Si is >99.99%.

[0013] Optionally, during smelting, Co is first added for the first smelting to form a first smelting system, and the smelting time is 40-50 min; Cu is added to the first smelting system for the second smelting to form a second smelting system, and the smelting time is 5-10 min; Si and the remaining alloy raw material components are added to the second smelting system for the third smelting to form a third smelting system, and the smelting time is 25-40 min.

[0014] Optionally, the temperatures of the first smelting, the second smelting and the third smelting are all 2300-2500° C.; and the first smelting, the second smelting and the third smelting are all induction smelting.

[0015] Optionally, the post-treatment includes grinding away the surface oxide layer of the Cu-Co-Si alloy after the aging treatment.

[0016] Optionally, the solution temperature used in the solution treatment is 1020±20°C, and the solution time is 60±5min; the heating rate used in the solution treatment is 5-8°C / min.

[0017] Optionally, the aging temperature used in the aging treatment is 200-600°C, and the aging time is 0.5-12h; the heating rate used in the aging treatment is 5-10°C / min.

[0018] In a second aspect, the present invention provides a high-hardness and high-conductivity Cu-Co-Si alloy, which is prepared by the preparation method of the high-hardness and high-conductivity Cu-Co-Si alloy.

[0019] The application of the technical solution of the present invention has at least the following beneficial effects:

[0020] (1) The present invention provides a method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy, which can prepare a Cu-Co-Si alloy with excellent comprehensive properties of high hardness and high conductivity, and has great application value. Specifically, step S1 is used to introduce the Co element into the Cu-Co-Si alloy prepared by smelting; step S2 is used for solid solution treatment to facilitate the improvement of the solid solubility of Co atoms and Si atoms in the copper matrix. The copper alloy structure after solid solution treatment is more uniform and the performance of the copper alloy is more stable; step S3 is used for aging treatment to promote the precipitation of compounds formed by Co and Si from the copper alloy to improve the electrical conductivity of the copper matrix, and at the same time, the precipitates form a second phase to strengthen and improve the hardness of the copper matrix. In addition, the preparation method adopted by the present invention is simple in process and easy to operate.

[0021] (2) The aging temperature used in the aging treatment of the present invention is 200-600°C, and the aging time is 0.5-12h; wherein, the aging temperature used in the present invention can promote as much as possible the precipitation of Co and Si compounds from the copper alloy to improve the electrical conductivity of the copper matrix, and at the same time precipitate to form a second phase reinforcement to improve the hardness of the copper matrix; the aging time used in the present invention can avoid the precipitation phase being too large, thereby improving the strength of the copper alloy.

[0022] (3) The present invention controls the addition of appropriate amounts of trace elements such as Mg, P and Cr in the alloy raw material composition, which can increase the nucleation density of the precipitation phase of the Cu-Co-Si alloy, promote the precipitation of the precipitation phase, slightly increase the electrical conductivity, and at the same time form inclusion particles, inhibit grain growth, and improve the hardness of the copper alloy.

[0023] (4) In the present invention, Co is first added for the first smelting, Cu is then added for the second smelting, and finally Si and the remaining alloy raw material components are added for the third smelting, so as to ensure that a uniform melt is formed by smelting, and a Cu-Co-Si alloy in which the alloy raw material components are uniformly dispersed is prepared. DETAILED DESCRIPTION

[0024] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention. Embodiment 1:

[0025] A method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy, comprising:

[0026] Step S1, melting the alloy raw material components with the required mass percentage to prepare Cu-Co-Si alloy;

[0027] Step S2, subjecting the prepared Cu-Co-Si alloy to a solid solution treatment;

[0028] Step S3, subjecting the Cu-Co-Si alloy after the solution treatment to aging treatment;

[0029] Step S4, post-treating the Cu-Co-Si alloy after the aging treatment to obtain the target product.

[0030] The required mass percentages of the alloy raw material components include 2.01% Co, 0.5% Si, 0.01% Mg, 0.02% P, 0.02% Cr, 0.01% O, 0.02% impurity and 97.41% Cu; wherein the impurities include Fe and C, etc.

[0031] The purity of the Co is >99.97%; the purity of the Cu is >99.95%; and the purity of the Si is >99.99%.

[0032] During smelting, Co is first added for the first smelting to form a first smelting system, and the smelting time is 45 minutes; Cu is added to the first smelting system for the second smelting to form a second smelting system, and the smelting time is 5 minutes; Si and the remaining alloy raw material components are added to the second smelting system for the third smelting to form a third smelting system, and the smelting time is 30 minutes.

[0033] The temperatures of the first smelting, the second smelting and the third smelting are all 2400° C.; the first smelting, the second smelting and the third smelting are all induction smelting.

[0034] The post-treatment includes grinding away the surface oxide layer of the Cu-Co-Si alloy after the aging treatment.

[0035] The solution temperature used in the solution treatment is 1020°C, and the solution time is 60 minutes; the heating rate used in the solution treatment is 5°C / min. Specifically, the tubular furnace is heated to 1020°C at a heating rate of 5°C / min, the Cu-Co-Si alloy is sealed in a quartz tube, high-purity argon gas is introduced, and the quartz tube is placed in a tubular furnace at 1020°C for 60 minutes of solution treatment to dissolve as many Co atoms and Si atoms as possible in the copper matrix. Then, the quartz tube is immediately taken out, and the quartz tube is placed in room temperature water within 5 seconds, and the quartz tube is broken in the water so that the Cu-Co-Si alloy is completely in contact with water, and water quenched to room temperature.

[0036] The aging temperature used in the aging treatment is 500°C, the aging time is 1h; the heating rate used in the aging treatment is 8°C / min. The KSL-1200X box furnace is heated to 500°C at a heating rate of 8°C / min, and the Cu-Co-Si alloy after solution treatment is placed in a box furnace at 500°C and kept warm for 1h. Since the solid solubility of Co in the copper matrix is ​​extremely low at this aging temperature, the aging temperature can promote as much as possible the formation of Co and Si compounds to precipitate from the copper alloy to improve the conductivity of the copper matrix, and at the same time precipitate to form a second phase strengthening to improve the hardness of the copper matrix. Then take out the quartz tube within 5s and break it, so that the Cu-Co-Si alloy is exposed to the air and air-cooled to room temperature. Embodiment 2:

[0037] The difference from Example 1 is that the aging time adopted in the aging treatment is 3 hours. Embodiment 3:

[0038] The difference from Example 1 is that the aging time adopted in the aging treatment is 5 hours. Embodiment 4:

[0039] Different from Example 1, the aging temperature used in the aging treatment is 350° C. and the aging time is 4 hours. Embodiment 5:

[0040] Different from Example 1, the aging temperature used in the aging treatment is 350° C. and the aging time is 8 h. Embodiment 6:

[0041] Different from Example 1, the aging temperature used in the aging treatment is 350° C. and the aging time is 12 h.

[0042] Comparative Example 1:

[0043] The difference from the first embodiment is that the aging treatment in step S3 is not provided.

[0044] Comparative Example 2:

[0045] Different from Example 1, step S2 of solution treatment and step S3 of aging treatment are not provided.

[0046] The target products prepared in Examples 1-6 and Comparative Examples 1-2 were subjected to conductivity tests and hardness tests, respectively. The test results are shown in Table 1. The conductivity test method is as follows: the conductivity is measured using a D60K-1201 digital metal conductivity meter. According to the instrument measurement requirements, the specimen thickness is >1.5mm, and the specimen plane width is >φ16mm. Therefore, the Cu-Co-Si target product is cut into discs with a sample size of 2mm thick and φ=20mm. The hardness test method is as follows: the hardness is measured using a MicroMet5104 microhardness tester. The sample size is the same as the sample size for measuring conductivity. The loading force is set to 100g and the loading time is set to 15s.

[0047] Table 1 Conductivity test and hardness test results

[0048]

[0049] It can be seen from the data in Table 1 that, compared with Comparative Examples 1-2, the present invention can prepare Cu-Co-Si alloys with excellent comprehensive properties of high hardness and high conductivity in Examples 1-6. In Comparative Example 1, step S3 aging treatment is not provided, so that the prepared Cu-Co-Si alloy has a significant decrease in hardness and electrical conductivity; in Comparative Example 2, step S2 solid solution treatment and step S3 aging treatment are not provided, so that the prepared Cu-Co-Si alloy has a further decrease in hardness performance. This is because the aging treatment of step S3 can promote the precipitation of compounds formed by Co and Si from the copper alloy to improve the electrical conductivity of the copper matrix, thereby improving the electrical conductivity of the Cu-Co-Si alloy; at the same time, the precipitate forms a second phase reinforcement to improve the hardness of the copper matrix, thereby improving the hardness performance of the Cu-Co-Si alloy. The solid solution treatment of step S2 is adopted to facilitate the improvement of the solid solubility of Co atoms and Si atoms in the copper matrix. The microstructure of the copper alloy after the solid solution treatment is more uniform, which can further cooperate with step S3 to improve the hardness performance of the Cu-Co-Si alloy.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy, characterized in that: include: Step S1, melting the alloy raw material components with the required mass percentage to prepare Cu-Co-Si alloy; Step S2, subjecting the prepared Cu-Co-Si alloy to a solid solution treatment; Step S3, subjecting the Cu-Co-Si alloy after the solution treatment to aging treatment; Step S4, post-treating the Cu-Co-Si alloy after the aging treatment to obtain a target product; The alloy raw material components of the required mass percentage include Co content of 1.0% to 3.0%, Si content ≤0.8%, Mg content ≤0.02%, P content ≤0.05%, Cr content ≤0.05%, O content ≤0.02%, impurity content ≤0.05% and balance Cu; During smelting, Co is first added for the first smelting to form a first smelting system, and the smelting time is 40-50 minutes; Cu is added to the first smelting system for the second smelting to form a second smelting system, and the smelting time is 5-10 minutes; Si and the remaining alloy raw material components are added to the second smelting system for the third smelting to form a third smelting system, and the smelting time is 25-40 minutes; The temperatures of the first smelting, the second smelting and the third smelting are all 2300-2500° C.; the first smelting, the second smelting and the third smelting are all induction smelting.

2. The method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy according to claim 1, characterized in that: The Si content is 0.1% to 0.8%; the Mg content is 0.01% to 0.02%; the P content is 0.02% to 0.05%; the Cr content is 0.02% to 0.05%; and the O content is 0.01% to 0.02%.

3. The method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy according to claim 1, characterized in that: The purity of the Co is >99.97%; the purity of the Cu is >99.95%; and the purity of the Si is >99.99%.

4. The method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy according to claim 1, characterized in that: The post-treatment includes grinding away the surface oxide layer of the Cu-Co-Si alloy after the aging treatment.

5. The method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy according to any one of claims 1 to 4, characterized in that: The solution temperature used in the solution treatment is 1020±20°C, and the solution time is 60±5min; the heating rate used in the solution treatment is 5-8°C / min.

6. The method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy according to claim 5, characterized in that: The aging temperature used in the aging treatment is 200-600°C, and the aging time is 0.5-12h; the heating rate used in the aging treatment is 5-10°C / min.

7. A high-hardness and high-conductivity Cu-Co-Si alloy, characterized in that: The alloy is prepared by the method for preparing a high-hardness and high-conductivity Cu-Co-Si alloy as described in claim 6.

Citation Information

Patent Citations

  • Cu-Co-Si-BASED COPPER ALLOY EXCELLENT IN STRENGTH, ELECTRIC CONDUCTIVITY AND BENDING WORKABILITY AND METHOD FOR MANUFACTURING THE SAME

    JP2012041562A